2009
DOI: 10.1248/bpb.32.493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methotrexate Treatment on Expression Levels of Organic Anion Transporter Polypeptide 2, P-Glycoprotein and Bile Salt Export Pump in Rats

Abstract: High-dose methotrexate (HDMTX) chemotherapy with leucovorin (LV) rescue has been used as a therapeutic strategy in oncology since the 1970s. Adverse reactions following extension of methotrexate (MTX) elimination are a crucial problem in HDMTX chemotherapy. MTX is a substrate for drug transporters, which are multidrug resistance protein 2 (Mrp2), organic anion transporter polypeptide 2 (Oatp2) and other transporters. We previously reported that MTX treatment downregulated the expression level of Mrp2 in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…That's while, the histological manifestations (Figures 2 C, D) confirmed the diagnosis of liver damage due to methotrexate use. In consistent with Shibayama and coauthors studies [26,27], since these enzymes are intracellular, they enter the serum when cell damage occurs [28]. Therefore, any reduction or increase in serum levels is considered abnormal compared to the control group.…”
Section: Discussionmentioning
confidence: 60%
“…That's while, the histological manifestations (Figures 2 C, D) confirmed the diagnosis of liver damage due to methotrexate use. In consistent with Shibayama and coauthors studies [26,27], since these enzymes are intracellular, they enter the serum when cell damage occurs [28]. Therefore, any reduction or increase in serum levels is considered abnormal compared to the control group.…”
Section: Discussionmentioning
confidence: 60%
“…1). 10,11) Expression levels of the protein are described as a percentage of the corresponding water-treated group (Table 3). Acetic acid, black vinegar and moromi treatments showed Each group was treated as follows: water, distilled water was given at a dose of 10 ml/kg; acetic acid, 1.5 ml of 0.23% acetic acid (pH 3.5) was diluted with 8.5 ml distilled water, and the diluted solution was given at a dose of 10 ml/kg; black vinegar, 1.5 ml concentrated black vinegar solution (pH 3.5) was diluted with 8.5 ml distilled water, and the diluted solution was given at a dose of 10 ml/kg; moromi, 50 mg moromi suspended in 10 ml distilled water, and the suspension was given at a dose of 10 ml/kg.…”
Section: Resultsmentioning
confidence: 99%
“…As a positive control treatment, dexamethasone was intraperitoneally injected at a dose of 50 mg/kg for consecutive 4 days 8,9) and methotrexate was intraperitoneally injected once at a dose of 150 mg/kg. 10,11) Dexamethasone-treated rats were killed the day after 4-day treatment. Methotraxatetreated rats were killed on day 4 after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous reports have shown that various apical efflux drug transporters expressed in the kidney, such as P-glycoprotein (P-gp), have a pivotal role in MTX excretion and detoxification (Leslie et al, 2005;Shibayama et al, 2009) and may participate as well in multidrug resistance against cancer chemotherapy. Therefore, P-gp might be a target for drug interaction and its up-regulation might participate in increasing MTX elimination, thus ameliorating renal toxicity.…”
Section: Introductionmentioning
confidence: 99%